005 Intravenous thrombolysis in acute ischaemic stroke: experience in a developing country. Issue 3 (9th February 2012) - Dey, K
Abstract : Aims and Objectives: This is an observational study of the patients thrombolysed in a multispeciality hospital in private sector in India. Materials and Method: The study was carried out in a 400-bedded hospital in the private sector where intravenous throbolysis programme and a dedicated stroke care was started in January 2010. The stroke patients have been clerked in on a standardised proforma displaying the NIH Stroke Scale. Patients with ischaemic strokes presenting within four and half hours without any contraindication have been thrombolysed using rtPA (Actilyse) at 0.9 mg/kg of body weight, 10% given as a bolus and the rest as infusion over 1 h. Results: Nine patients have been thromblysed between January 2010 and June 2011: six male and three female. Mean symptom onset to thrombolysis time is 2.77 h. Seven patients had middle cerebral artery infarcts while two patients had both middle and posterior cerebral aretrial territory infarcts. Of them one had lacunar infarcts in both MCA and PCA territory and the other had large PCA infacts with a lacunar infarct in the MCA terrotory. CT scan brain was the initial neuroimaging of choice except in one case where diffusion MR was obtained emergently because of the fluctuating motor weakness. Of the nine patients none had any fatal ICH. One patient had nonfatal ICH and subsequently made a full recovery. One patient died out of hospital a few months later of an unrelated cause. The other eight patients are all independently mobile at 3 months. Conclusions: This study shows that it is feasible to set up an intravenous thrombolysis programme in a private sector hospital in a developing country and it is a safe procedure if the protocol is followed strictly. Three important barriers to thrombolysis have been identified: delay in emergency CT scans, physicians' attitude towards thrombolysis and lack of awareness amongst the laity of the stroke and thrombolysis.